SEMIOTIC STUDY OF SUFISTIC VERBAL EXPRESSION LIVING SUFISM AT THE AT-TAQY JEPARA ISLAMIC BOARDING SCHOOL - Atika Ulfa Adlina; Luthfi Rahman (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
The expressions of Sufi spiritual experience are often shown on verbal media (Sufi language) such as poetry or simple expressions, etc. Reading the expressions requires careful reading so that the esoteric meaning can be captured. The purpose of this article is to read the writing of the walls in the at-taqy Islamic boarding school. To be able to do this reading, the semiotic method is used. Similar research has been carried out, but what makes this study unique is that the writing of the wall is a living sufism at the At-Taqy Islamic Boarding School. The result is the writing of the walls in the at-Taqy Islamic boarding school loaded with basic concepts of Sufism, namely about Fana, Wahdatul Wujud, Taubat and Muhasabah.